Role of prostaglandins in nociception during ischaemia and reperfusion of the rat's tail - Gelgor, Linda (My University, 2014)
I have investigated the effects o f both systemic and intracerebroventricular administration o f non-steroidal anti-inflammatory drugs (NSAIDs), o f varying therapeutic potency, on i) nociception during tail ischaemia and ii) hyperalgesia to a noxious thermal stimulus, evident during reperfusion of the receptive field on the tail, in conscious Sprague-Dawley rats. NSAIDs were found to attenuate the hyperalgesia evident during reperfiision o f the tail, whilst having no effect on the escape latency to a noxious ischaemic stimulus or on the tail flick latency in the absence of tail ischaemia. The intracerebroventricular doses required to attenuate reperfiision hyperalgesia were 2-3 orders o f magnitude less than those required by systemic administration for the same drugs. Using mechanical search stimuli, I located neurones in the dorsal horn of the spinal cord of rats with receptive fields in the tail. Neuronal responses to noxious and innocuous mechanical stimulation, as well as to noxious thermal stimulation before ischaemia and during reperfusion after ischaemia, were assessed. Of the population of neurones I examined, only a minority responded to thermal stimulation before ischaemia, and during reperfiision the neurones became more sensitive to mechanical stimuli, but not to noxious thermal stimuli. Furthermore, the neurones exhibited a decreased sensitivity to mechanical stimulation during ischaemia. Application of NSAIDs to the spinal cord did not alter the response properties of the neurones during receptive field ischaemia, but decreased receptive field size and reduced spontaneous and evoked activity during reperfusion of the tail. I have shown that the neurochemical mechanisms underlying nociception during ischaemia and reperfusion of the rat tail are different. While prostaglandins appear to pla] .0 role in mediating nociception during ischaemia, they are mediators of the hyperalgesia and neuronal hypersensitivity evident during receptive field reperfusion.
Keywords: Pain Measurement.; Prostaglandins